The Role of Productive Zakat in Fostering a Green Creative Economy: A Literature Review on Its Implementation in East Java - Rofiq Guntur Wicaksono (GERASI INSAN NUSANTARA, 2026)
This study examines the role of productive zakat within a Green Zakat Framework in supporting the development of a green creative economy among mustahik in East Java. The research addresses the need to integrate Islamic social finance with sustainable development principles, particularly in response to environmental degradation and socio-economic inequality. Using a qualitative literature study approach, this research analyzes conceptual foundations based on maqasid al-shariah, especially hifz al-bi’ah, alongside empirical practices of productive zakat distribution. The findings indicate that productive zakat has significant potential to enhance mustahik welfare, promote entrepreneurial capacity, and foster creative economic activities. Furthermore, although current zakat practices in East Java primarily focus on economic empowerment, they provide a strong foundation for integrating environmentally sustainable practices. The study concludes that the Green Zakat Framework offers a strategic model to transform zakat into an instrument that simultaneously advances economic independence, social equity, and environmental sustainability. Future development requires structured indicators, institutional strengthening, and policy integration to optimize its implementation